(untitled) (Revista Tempo e Argumento, 2009)
Ana Luiza Setti Reckziegel, Universidade de Passo Fundo Ana Paula Vosne Martins, Universidade Federal do Paraná Antonio Emilio Morga, Universidade Federal do Amazonas Antônio Manoel Elíbio Júnior, Universidade do Sul de Santa Catarina Clarícia Otto, Universidade Federal de Santa Catarina Elisom Antônio Paim, Universidade Comunitária Regional de Chapecó Geni Rosa Duarte, Universidade do Oeste do Paraná Janine Gomes da Silva, Universidade da Região de Joinville José Roberto Severino, Universidade Regional de Blumenau Mara Rúbia Sant’Anna, Universidade do Estado de Santa Catarina Mauríco Lissovsky, Universidade Federal do Rio de Janeiro